Response to Comment on: FLT3 ligand kinetic profile predicts response to treatment in patients with high-risk myelodysplastic syndrome / chronic myelomonocytic leukemia receiving CPX-351: a study from the Groupe Francophone des Myélodysplasies - Pierre Peterlin; Maxime Jullien (Haematologica)
Not available.